Energy storage of DFIG based wind farm using D-STATCOM - Kaoutar Rabyi; Hassane Mahmoudi (Institute of Advanced Engineering and Science, 2019)
To accommodate the regularity of wind energy; a storage device is required for the wind turbine. This paper proposesa constant power control for wind farm based Doubly Fed Induction Generator, the suggested storage device is supercapacitor which is connected to every wind turbine of the wind farm, it provides output power stability and compensates the deviations between the available wind energy input and the desired active power output. A Distribution – Static Synchronous Compensator (D-STATCOM) is connected at the point of connection of the wind farm, it controls the active and reactive power according to the demand from orpower generation to the electrical grid. The coordinated approach between the supercapacitors and the D-STATCOM mitigates the voltage magnitude fluctuations of the wind farm and provides support to the active power. Simulation studies are carried out inMATLAB/Simulink.